Clinical pharmacology of levetiracetam for the treatment of epilepsy. Issue 4 (July 2009) - Stockis, Armel; Lu, Sarah; Tonner, Françoise; Otoul, Christian
Levetiracetam is an antiepileptic drug that is mainly indicated for the adjunctive treatment of partial-onset seizures in adults and children and of myoclonic and primary generalized tonic–clonic seizures in patients with idiopathic generalized epilepsy. In Europe, levetiracetam is also indicated as monotherapy for partial-onset seizures in patients with newly diagnosed epilepsy. Synaptic vesicle protein 2A is the primary molecular target for its anticonvulsive effect but additional mechanisms may also contribute. Recent clinical and pharmacokinetic developments for levetiracetam are reviewed in specific populations, including the effects of age, pregnancy, birth and lactation, pediatric development, and ethnic origin. The population pharmacokinetics of levetiracetam and drug–drug interactions have been explored across large adult and pediatric populations. The exposure–response relationship has also been characterized in adults and children through nonlinear mixed-effects modeling. Finally, new formulations including intravenous infusion and extended-release once-daily tablets have been compared with immediate-release tablets and oral solution, and can be used interchangeably.